Importance of abiotic factors and hydroperiod for the zooplankton community from ponds with different hydrological dynamics - José Gabriel Melo da Cruz; Fernanda Zucoloto Domingues; Luisa Rodrigues dos Santos; Rayanne Barros Setubal; Elder de Oliveira Sodré; Reinaldo Luiz Bozelli (Acta Limnologica Brasiliensia)
Abstract: Aim The increasing impact on natural environments has led to changes in ecosystem characteristics. When not properly understood and managed, these changes can negatively affect the dynamics of aquatic environments, particularly small ones such as temporary ponds. Hydroperiod can influence the structure of aquatic ecosystems and the factors determining species occurrence in these water bodies. Within this context, studies assessing the influence of hydroperiod become highly relevant. This study evaluates how zooplankton species are distributed across five ponds with different hydroperiods in the Restinga de Jurubatiba National Park and the importance of water retention time for the taxonomic and functional diversity of this community. Methods We indirectly assessed water retention time through daily temperature measurements over three years and analyzed the main limnological parameters. The zooplankton community was sampled from the five studied ponds, and its diversity was evaluated using species richness (S), Shannon-Wiener diversity index (H’), functional richness (FRic), functional divergence (FDiv), and functional dispersion (FDis). Results We observed that even though the ponds are part of the same natural mosaic, they exhibit distinct characteristics. Abiotic factors such as water salinity and a more unstable hydroperiod negatively impacted zooplankton taxonomic and functional diversity, as shown by the integrated analysis of both diversity components. The highest taxonomic diversity values were found in ponds with intermediate water retention conditions (seasonal droughts). Conclusions Our results indicate that seasonal environments favor the co-occurrence of species from both perennial and ephemeral ponds, showing higher Shannon-Wiener diversity index (H’), functional richness (FRic), and functional divergence (FDiv) values when analyzed through an integrated approach. Furthermore, we observed that even under the same regional species pool, differences in desiccation frequency were sufficient to determine variations in the zooplankton community.